CARBON STOCK ASSESMENT ON MANGROVE FOREST ECOSYSTEM IN JORONG UJUANG LABUANG DISTRICT AGAM WEST SUMATERA PROVINCE - Oktaviona, Silvi; Amin, Bintal; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Mangrove is a tree that normally grows in the intertidal zone of marine coastal environments. This study aims to estimate the carbon content of mangrove forest ecosystems within a certain area, to analyze biomass differences, carbon stocks and CO2 uptake and to analyze the effect of mangrove density on biomass, carbon stock and CO2 uptake. This research held on February 2017 by survey method and used the data of mangrove species, it’s number and diameter of breast height (DBH) on each sub plot. Measurement of mangrove biomass was done allometric equation method. The result of carbon stock and CO2 uptake in mangrove indecates that Station III was higher than Station I and II. The average yield of mangrove carbon stock and CO2 uptake is 1333,99 ton / ha and 4891.30 ton / ha. For the highest soil organic carbon is found in Station 1 with an average soil organic carbon of 1446.75 tons / ha. The density of mangrove biomass, carbon content and CO2 uptake which has a strong relationship. The content of biomass, mangrove carbon and CO2 uptake were significantly different (p <0.05) between stations. Keywords: Mangrove, Carbon, Jorong Ujuang Labuang